A multifunctional conductive foam

By using graphene and nano -metal cobalt as a conductive, and through modification and cross -linking technology, the existing conductive foam has poor conductivity and insufficient flame retardant performance, and achieves high -performance conductive and flame retardant effects.

CN118813157BActive Publication Date: 2025-01-21SUZHOU WANHE ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411281475.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-21
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The existing conductive foam has poor conductivity and unevenness and insufficient flame retardant performance, which cannot meet the demand for high-performance shielding and flame retardant for electronic products.

Method used

Graphene and nanometal cobalt are used as conductive agents. Through the modification treatment of oleic acid and thiophene, a conductive agent with polythiophene coating nanocobalt is formed, and cross-linked with melamine polyphosphate to form a multifunctional conductive foam.

Benefits of technology

It improves the conductivity and mechanical properties of the foam, enhances its flame retardant performance, reaches the UL94-HF1 level, and meets the needs of electronic products for high-performance shielding and flame retardant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118813157B_ABST
    Figure CN118813157B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of foam, and provides a multifunctional conductive foam, which includes conductive cloth, foam, adhesive layer and isolation layer from top to bottom, and the foam includes: 100 parts of polyether polyol, 25-35 parts of isocyanate, 10-18 parts of flame retardant conductive agent, 1-2 parts of foaming agent, 2-2.5 parts of catalyst, 1-5 parts of antioxidant and 2-5 parts of foam stabilizer. The flame retardant conductivity is prepared by cross-linking melamine polyphosphate with graphene-loaded nano-cobalt conductive agent. The foam of the present invention uses graphene and nano-metal cobalt to replace carbon black as conductive additives, which reduces the amount of conductive agent added in polyurethane foam and improves the mechanical properties of the foam. The present invention uses nano-nickel synergistic flame retardant melamine polyphosphate, so that its limiting oxygen index reaches 33%, and the flame retardant grade reaches UL94-HF1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of foam, and in particular relates to a multifunctional conductive foam. Background Art

[0002] Foam is a material made of foamed plastic particles, referred to as foam. Foam has a series of characteristics such as elasticity, light weight, fast pressure-sensitive fixation, easy use, and easy bending.

[0003] Conductive foam is particularly suitable for occasions with limited capacity and closing pressure, and has low cost. It is particularly suitable for use in occasions that require good fit and high-performance shielding. It can be widely used in electronic chassis, housings, indoor chassis, industrial equipment, laptops, mobile communication equipment, etc. However, the existing conductive foam has poor conductivity and uneven conductivity, which seriously affects the shielding effect of the conductive foam. On the other hand, electronic products are constantly updated, their working components are becoming more and more sophisticated, the speed and efficiency of work are getting higher and higher, and the heat generation is also getting higher and higher. Therefore, it is not only required to be equipped with corresponding heat dissipation foam, but also to have flame retardant ability to avoid excessive temperature and cause flammable products to become flammable.

[0004] Most of the conductive foams in the prior art use conductive carbon black as the conductive medium. Therefore, not only is the amount of conductive medium added too large, it is easy to contaminate the contact objects and reduce the mechanical properties of the foam. However, if the amount of carbon black added is reduced, its conductivity will be low. At the same time, they do not have flame retardant properties and cannot fully meet market requirements. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide a multifunctional conductive foam to solve the problems of poor flame retardancy and low electrical conductivity of the conductive foam in the prior art.

[0006] The purpose of the present invention is mainly achieved through the following technical solutions:

[0007] A multifunctional conductive foam, which comprises a conductive cloth, a foam, an adhesive layer and an isolation layer from top to bottom;

[0008] The foam includes: 100 parts of polyether polyol, 25-35 parts of isocyanate, 10-18 parts of flame retardant conductive agent, 1-2 parts of foaming agent, 2-2.5 parts of catalyst, 1-5 parts of antioxidant and 2-5 parts of foam stabilizer;

[0009] The preparation method of the flame retardant conductive agent comprises the following steps:

[0010] S1: 2-4 portions of nano-cobalt powder are put into a reactor, and a mixed solution of oleic acid and anhydrous ethanol is added for ultrasonic dispersion. After the reaction is completed, the product is filtered and washed with anhydrous ethanol, and vacuum dried to obtain oleic acid-nano-cobalt; the mass ratio of nano-cobalt powder to oleic acid is 12-20:1;

[0011] S2: ultrasonically dispersing 2-4 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 5-8 parts of thiophene and 0.1-0.2 parts of hydrogen peroxide, stirring for reaction, and then performing solid-liquid separation, washing the obtained solid with ethanol and drying it to obtain polythiophene-coated nano cobalt;

[0012] S3: pre-treating the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine, then rinsing with anhydrous ethanol and drying for standby use; ultrasonically dispersing 10 parts of the pre-treated graphene and 2-4 parts of the polythiophene-coated nano-cobalt in a reactor filled with an ethanol aqueous solution and stirring evenly, then adding 0.1-0.3 parts of sodium sulfite to the reactor, stirring and reacting under a nitrogen atmosphere, then filtering and washing the solid with anhydrous ethanol, and vacuum drying; obtaining a graphene-loaded nano-cobalt conductive agent;

[0013] S4: 30-40 parts of melamine polyphosphate, 8-10 parts of resorcinol and 10 parts of a conductive agent are ultrasonically dispersed in acetone, and a cross-linking reaction is carried out for a period of time, and then centrifuged to separate the solid and liquid, and the solid is washed with ethanol and then dried to obtain a flame retardant conductive agent.

[0014] Preferably, the specific process of step S1 is to take 2-4 parts of nano cobalt powder and put it into a reactor, add a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9, and ultrasonically disperse it, react for 30-60 minutes, filter the product, wash it with anhydrous ethanol 2-3 times, and then vacuum dry it to obtain oleic acid-nano cobalt; the mass ratio of nano cobalt powder to oleic acid is 12-20:1.

[0015] Preferably, the specific process of step S2 is: ultrasonically disperse 2-4 parts of oleic acid-nano cobalt in 200 parts of deionized water, then add 5-8 parts of thiophene and 0.1-0.2 parts of hydrogen peroxide, stir and react at 40-60° C. for 40-60 minutes, then perform solid-liquid separation, wash the obtained solid with ethanol and then dry to obtain polythiophene-coated nano cobalt.

[0016] Preferably, the specific process of step S3 is: pre-treating the three-dimensional graphene foam in an air atmosphere for 2-5 minutes in a plasma treatment machine, then rinsing with anhydrous ethanol and drying for standby use; ultrasonically dispersing 10 parts of pre-treated graphene and 2-4 parts of polythiophene-coated nano-cobalt in a reactor containing 100 parts of ethanol aqueous solution and stirring evenly, then adding 0.1-0.3 parts of sodium sulfite to the reactor, stirring and reacting for 30-60 minutes under a nitrogen atmosphere, then filtering and washing the solid with anhydrous ethanol 2-3 times and then vacuum drying; obtaining a graphene-loaded nano-cobalt conductive agent. The pre-treated graphene introduces functional groups such as hydroxyl and carboxyl, which is conducive to the subsequent reaction.

[0017] Preferably, the specific process of step S4 is: ultrasonically disperse 30-40 parts of melamine polyphosphate, 8-10 parts of resorcinol and 10 parts of conductive agent in acetone, uniformly react at 50-70°C for 3-6 hours, centrifuge for solid-liquid separation, wash the solid with ethanol 2-3 times and then dry to obtain a flame retardant conductive agent.

[0018] Preferably, the conductive fabric layer is plain conductive fabric with a thickness of 40 μm-120 μm; the adhesive layer is a pressure-sensitive adhesive or a hot-melt adhesive with a thickness of 10-15 μm; and the isolation layer is release paper with a thickness of 20-30 μm.

[0019] Preferably, the antioxidant is one of antioxidant 5057, antioxidant 168 and antioxidant 1010.

[0020] Preferably, the foam stabilizer is one or more of polyacrylamide and dimethyl silicone oil.

[0021] Preferably, the catalyst is one or more of stannous octoate, stannous isooctanoate and dibutyltin dilaurate. The blowing agent is water or a mixture of water and 1,1-dichloro-1-fluoroethane.

[0022] Principle of the present invention:

[0023] Melamine polyphosphate (MPP) is a nitrogen-phosphorus flame retardant whose molecules contain gas source (melamine) and acid source (phosphoric acid) substances. The flame retardant begins to decompose at about 355°C, producing nitrogen-containing inert gas and polyphosphoric acid. Inert gas can effectively dilute oxygen and combustible gas in the gas phase, playing a role in gas phase flame retardancy; while polyphosphoric acid can promote the formation of an expansive carbon layer in the polymer matrix, effectively isolating heat and mass transfer in the condensed phase, and playing a role in condensed phase flame retardancy. Through the gas phase-condensed phase synergistic mechanism, the flame retardant properties of polymer materials can be significantly improved.

[0024] Nano cobalt exhibits excellent electromagnetic shielding effect due to its excellent electrical conductivity and magnetism, and has good catalytic performance. It can provide active sites, adsorb and activate melamine polyphosphate molecules, thereby reducing the activation energy of the decomposition reaction and accelerating the reaction. This allows melamine polyphosphate to decompose at a relatively low temperature (200-250°C), increases the rate of flame-retardant gas and carbon layer generation, and effectively prevents the spread of flames. However, since nano cobalt has a large specific surface area and high surface energy, it is easy to agglomerate, and traditional mechanical means are difficult to effectively disperse it again. In addition, nano cobalt has poor compatibility with polymer materials, which further aggravates the agglomeration problem. To solve these problems, the present invention uses oleic acid to modify and protect nano cobalt. Oleic acid contains unsaturated double bonds and carboxyl groups, which can form a monomolecular film with nano cobalt, and is coated on the surface of metal nano cobalt in the form of ionic bonds, increasing the distance between nano cobalt particles and electrostatic repulsion, and preventing agglomeration between particles. At the same time, when compounded with the matrix resin, the unsaturated double bonds in oleic acid can be opened by the action of an initiator or heat or mechanical energy, and a series of chemical reactions such as grafting and crosslinking with the polyurethane matrix occur, further promoting better combination of nano cobalt and the polyurethane matrix. On the other hand, nano cobalt is easily oxidized, which affects its electrical conductivity and catalytic activity. Therefore, the present invention forms a structure of polythiophene-coated nano cobalt through in-situ polymerization of thiophene and oleic acid-nano cobalt. Since polythiophene has good electrical conductivity, compared with other polymer materials, coating nano cobalt will not affect its electrical conductivity.

[0025] Graphene has become an excellent conductive material with its extremely high electrical conductivity. Adding graphene to polyurethane foam can significantly improve the conductivity of the material. Compared with traditional carbon black conductive additives, the use of graphene can greatly reduce the amount of addition while maintaining the mechanical properties of polyurethane foam. The present invention uses three-dimensional graphene foam as a carrier to load nano-cobalt in its gaps and interlamellar. The conjugated π orbitals in the polythiophene molecular structure can be adsorbed with the conjugated regions in the graphene molecular structure through π-π interactions, so that nano-cobalt can be stably loaded on graphene. Finally, the graphene-loaded nano-cobalt conductive agent is cross-linked with melamine polyphosphate, so that it can stably play a synergistic flame retardant role in the polyurethane matrix.

[0026] Compared with the prior art, the present invention has at least the following beneficial effects:

[0027] The foam of the invention adopts graphene and nano-metal cobalt instead of carbon black as a conductive agent, thereby reducing the amount of conductive agent added in the polyurethane foam and improving the mechanical properties of the foam.

[0028] The present invention uses nano-nickel to synergistically flame retard melamine polyphosphate, so that its limiting oxygen index reaches 33%, and the flame retardant grade reaches UL94-HF1.

[0029] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0031] Figure 1 This is a schematic diagram of the structure of the multifunctional conductive foam layer of the present invention.

[0032] Figure numerals: 1-conductive cloth, 2-foam, 3-adhesive layer, 4-isolating layer. DETAILED DESCRIPTION

[0033] The technical scheme of the present invention is further described below in conjunction with specific embodiments, but the present invention should not be limited to these embodiments, unless otherwise described, all can be replaced by other equivalent or alternative features with similar purposes. Unless otherwise described, each feature is only an example in a series of equivalent or similar features. The terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by ordinary technicians in the field. In the following examples, unless otherwise specified, concentration % refers to mass percentage; the substances used can be obtained commercially. The technical scheme of the present invention is further described below in conjunction with specific embodiments, but the present invention should not be limited to these embodiments, unless otherwise described, all can be replaced by other equivalent or alternative features with similar purposes. Unless otherwise described, each feature is only an example in a series of equivalent or similar features. The terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by ordinary technicians in the field.

[0034] The reagents used in the present embodiment and comparative examples are as follows. Those skilled in the art can select appropriate reagents for substitution, which can also achieve the limitations of the present invention. The following reagent selection is not used to limit the present invention.

[0035] The polyether polyol was purchased from Shanghai Baiang Chemical Technology Co., Ltd. The model number was 1030, the hydroxyl value was 230-250 mgKOH / g, and the number average molecular weight was 1500-2000.

[0036] Isocyanate was purchased from Wanhua Chemical, hexamethylene diisocyanate, with a purity of 99%.

[0037] Oleic acid was purchased from Nanjing Shuguang Chemical Factory.

[0038] Graphene foam was purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd. with a porosity of 97% and a C / O atomic ratio of 40.

[0039] Nano-cobalt was purchased from Zhejiang Yamei Nanotechnology Co., Ltd. with a purity of 99.99% and an average particle size of 20 nm.

[0040] Thiophene was purchased from Suzhou Yaco Technology Co., Ltd.

[0041] Melamine polyphosphate was purchased from BASF, brand: Melapur 200-70 (N: 42%~44%, P: 12%~14%).

[0042] The conductive fabric is plain woven conductive fabric purchased from Guangdong Taikun New Material Technology Co., Ltd.

[0043] The method for preparing the multifunctional conductive foam of the present invention comprises the following steps:

[0044] The polyether polyol is vacuum dehydrated at 130-140° C. until the moisture content is no more than 0.5%, thereby obtaining the treated polyether polyol.

[0045] 2-2.5 parts of catalyst, 100 parts of polyether polyol and 1-5 parts of antioxidant are added into a reaction kettle, and reacted at 220-240° C. for 1-2 hours to obtain a reaction material.

[0046] 10-18 parts of flame retardant conductive agent, 25-35 parts of isocyanate, 1-2 parts of foaming agent and 2-5 parts of foam stabilizer are added to the reaction material for foaming at a foaming temperature of 80-85° C. and a reaction time of 20-30 minutes to obtain a foamed body.

[0047] The antioxidant can be one of antioxidant 5057, antioxidant 168 and antioxidant 1010.

[0048] The foam stabilizer can be one or more of polyacrylamide and dimethyl silicone oil.

[0049] The catalyst may be one or more of stannous octoate, stannous isooctanoate and dibutyltin dilaurate.

[0050] The blowing agent can be water or a mixture of water and 1,1-dichloro-1-fluoroethane.

[0051] The foamed body is subjected to a aging treatment at 40-60° C. to obtain foam.

[0052] Cut the foam into units with a width of 2 cm, a length of 10 cm and a thickness of 0.3 cm; the size can be customized according to actual customer needs and there is no restriction here.

[0053] Figure 1The schematic diagram of the layer structure of the multifunctional conductive foam of the present invention is shown, which at least comprises a conductive cloth 1, a foam 2, an adhesive layer 3 and an isolation layer 4 in sequence from the top.

[0054] Use a bonding machine to bond the cut foam 2 to the 40μm-120μm conductive cloth 1; evenly apply a 10-15μm thick adhesive layer 3 pressure-sensitive adhesive on the side of the foam 2 away from the conductive cloth, and then press the foam with the pressure-sensitive adhesive onto the 20-30μm thick isolation layer 4 release paper.

[0055] After completing the above steps, the multifunctional foam is obtained.

[0056] Specific examples of foam preparation are listed below to further illustrate the present invention.

[0057] Example 1

[0058] S1: Take 2 parts of nano cobalt powder and put them into a reactor, add a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9, and then disperse them by ultrasonic. After reacting for 30 minutes, filter and wash the product with anhydrous ethanol twice and then vacuum dry to obtain oleic acid-nano cobalt; the mass ratio of nano cobalt powder to oleic acid is 12:1.

[0059] S2: Ultrasonic dispersion of 2 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 5 parts of thiophene and 0.1 parts of hydrogen peroxide, stirring and reacting at 40°C for 40 minutes, and then performing solid-liquid separation. The obtained solid was washed with ethanol and then dried to obtain polythiophene-coated nano cobalt.

[0060] S3: Pre-treat the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine for 2 minutes, then rinse with anhydrous ethanol and blow dry for use; ultrasonically disperse 10 parts of the pre-treated graphene and 2 parts of polythiophene-coated nano-cobalt in a reactor filled with 100 parts of ethanol aqueous solution and stir evenly, then add 0.1 parts of sodium sulfite to the reactor, stir the reaction for 30 minutes under a nitrogen atmosphere, then filter and wash the solid with anhydrous ethanol twice and then vacuum dry; obtain a graphene-loaded nano-cobalt conductive agent.

[0061] S4: 30 parts of melamine polyphosphate, 8 parts of resorcinol and 10 parts of conductive agent are ultrasonically dispersed in acetone, uniformly reacted at 50°C for 3 hours, centrifuged for solid-liquid separation, and then washed with ethanol and dried to obtain a flame retardant conductive agent.

[0062] The polyether polyol was dehydrated under vacuum at 130° C. until the moisture content was 0.4%, thereby obtaining a treated polyether polyol.

[0063] 2 parts of catalyst stannous octoate, 100 parts of polyether polyol and 1 part of antioxidant 1010 were added into a reaction kettle, and reacted at 220° C. for 1 hour to obtain a reaction material.

[0064] 10 parts of flame retardant conductive agent, 25 parts of isocyanate, 1 part of foaming agent water and 2 parts of foam stabilizer dimethyl silicone oil were added to the reaction material for foaming at a foaming temperature of 80° C. and a reaction time of 20 min to obtain a foamed body.

[0065] The foamed body was aged at 40°C to obtain foam.

[0066] Example 2

[0067] S1: Take 4 parts of nano cobalt powder and put them into a reactor, add a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9, and then disperse them by ultrasonic. After reacting for 60 minutes, filter and wash the product with anhydrous ethanol for 3 times and then vacuum dry to obtain oleic acid-nano cobalt; the mass ratio of nano cobalt powder to oleic acid is 20:1.

[0068] S2: Ultrasonic dispersion of 4 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 8 parts of thiophene and 0.2 parts of hydrogen peroxide, stirring and reacting at 60°C for 60 minutes, and then performing solid-liquid separation. The obtained solid was washed with ethanol and then dried to obtain polythiophene-coated nano cobalt.

[0069] S3: Pre-treat the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine for 5 minutes, then rinse with anhydrous ethanol and blow dry for use; ultrasonically disperse 10 parts of the pre-treated graphene and 4 parts of polythiophene-coated nano-cobalt in a reactor filled with 100 parts of ethanol aqueous solution and stir evenly, then add 0.3 parts of sodium sulfite to the reactor, stir the reaction for 60 minutes under a nitrogen atmosphere, then filter and wash the solid with anhydrous ethanol three times and then vacuum dry; obtain a graphene-loaded nano-cobalt conductive agent.

[0070] S4: 40 parts of melamine polyphosphate, 10 parts of resorcinol and 10 parts of conductive agent are ultrasonically dispersed in acetone, uniformly reacted at 70°C for 6 hours, centrifuged for solid-liquid separation, then washed with ethanol and dried to obtain a flame retardant conductive agent.

[0071] The polyether polyol was dehydrated under vacuum at 140° C. until the moisture content was 0.4%, thereby obtaining a treated polyether polyol.

[0072] 2.5 parts of catalyst stannous isooctanoate, 100 parts of polyether polyol, and 5 parts of antioxidant 168 were added into a reaction kettle, and reacted at 240° C. for 2 hours to obtain a reaction material.

[0073] 18 parts of flame retardant conductive agent, 35 parts of isocyanate, 2 parts of a mixture of water and 1,1-dichloro-1-fluoroethane (9:2) as a foaming agent, and 5 parts of polyacrylamide as a foam stabilizer were added to the reaction material for foaming at a foaming temperature of 85°C and a reaction time of 30 minutes to obtain a foamed body.

[0074] The foamed body was aged at 60°C to obtain foam.

[0075] Example 3

[0076] S1: Take 3 parts of nano cobalt powder and put them into a reactor, add a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9, and then disperse them by ultrasonic. After reacting for 50 minutes, filter and wash the product with anhydrous ethanol twice and then vacuum dry to obtain oleic acid-nano cobalt; the mass ratio of nano cobalt powder to oleic acid is 15:1.

[0077] S2: Ultrasonic dispersion of 3 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 6 parts of thiophene and 0.15 parts of hydrogen peroxide, stirring and reacting at 50°C for 50 minutes, and then performing solid-liquid separation. The obtained solid was washed with ethanol and then dried to obtain polythiophene-coated nano cobalt.

[0078] S3: Pre-treat the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine for 4 minutes, then rinse with anhydrous ethanol and blow dry for use; ultrasonically disperse 10 parts of pre-treated graphene and 3 parts of polythiophene-coated nano-cobalt in a reactor filled with 100 parts of ethanol aqueous solution and stir evenly, then add 0.2 parts of sodium sulfite to the reactor, stir and react for 45 minutes under a nitrogen atmosphere, then filter and wash the solid with anhydrous ethanol 3 times and then vacuum dry; obtain a graphene-loaded nano-cobalt conductive agent.

[0079] S4: 35 parts of melamine polyphosphate, 9 parts of resorcinol and 10 parts of conductive agent are ultrasonically dispersed in acetone, uniformly reacted at 60°C for 5 hours, centrifuged for solid-liquid separation, then washed with ethanol and dried to obtain a flame retardant conductive agent.

[0080] The polyether polyol was dehydrated under vacuum at 135° C. until the moisture content was 0.3%, thereby obtaining a treated polyether polyol.

[0081] 2.3 parts of catalyst dibutyltin dilaurate, 100 parts of polyether polyol, and 2 parts of antioxidant 5057 were added into a reaction kettle, and reacted at 230° C. for 1.5 hours to obtain a reaction material.

[0082] 14 parts of flame retardant conductive agent, 30 parts of isocyanate, 1.5 parts of foaming agent water and 4 parts of foam stabilizer polyacrylamide were added to the reaction material for foaming at a foaming temperature of 82° C. and a reaction time of 25 min to obtain a foamed body.

[0083] The foamed body was aged at 50°C to obtain foam.

[0084] Example 4

[0085] S1: Take 3 parts of nano cobalt powder and put them into a reactor, add a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9, and then disperse them by ultrasonic. After reacting for 50 minutes, filter and wash the product with anhydrous ethanol twice and then vacuum dry to obtain oleic acid-nano cobalt; the mass ratio of nano cobalt powder to oleic acid is 18:1.

[0086] S2: Ultrasonic dispersion of 3 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 6 parts of thiophene and 0.15 parts of hydrogen peroxide, stirring and reacting at 50°C for 50 minutes, and then performing solid-liquid separation. The obtained solid was washed with ethanol and then dried to obtain polythiophene-coated nano cobalt.

[0087] S3: Pre-treat the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine for 4 minutes, then rinse with anhydrous ethanol and blow dry for use; ultrasonically disperse 10 parts of pre-treated graphene and 3 parts of polythiophene-coated nano-cobalt in a reactor filled with 100 parts of ethanol aqueous solution and stir evenly, then add 0.2 parts of sodium sulfite to the reactor, stir and react for 45 minutes under a nitrogen atmosphere, then filter and wash the solid with anhydrous ethanol 3 times and then vacuum dry; obtain a graphene-loaded nano-cobalt conductive agent.

[0088] S4: 38 parts of melamine polyphosphate, 9 parts of resorcinol and 10 parts of conductive agent are ultrasonically dispersed in acetone, uniformly reacted at 60°C for 5 hours, centrifuged for solid-liquid separation, then washed with ethanol and dried to obtain a flame retardant conductive agent.

[0089] The polyether polyol was dehydrated under vacuum at 135° C. until the moisture content was 0.4%, thereby obtaining a treated polyether polyol.

[0090] 2.3 parts of catalyst stannous octoate, 100 parts of polyether polyol, and 2 parts of antioxidant 1010 were added into a reaction kettle, and reacted at 230° C. for 1.5 hours to obtain a reaction material.

[0091] 16 parts of flame retardant conductive agent, 30 parts of isocyanate, 1.5 parts of foaming agent water and 3 parts of foam stabilizer dimethyl silicone oil were added to the reaction material for foaming at a foaming temperature of 83° C. and a reaction time of 25 min to obtain a foamed body.

[0092] The foamed body was aged at 50°C to obtain foam.

[0093] Comparative Example 1

[0094] S2: Ultrasonic dispersion of 3 parts of nano-cobalt in 200 parts of deionized water, then adding 6 parts of thiophene and 0.15 parts of hydrogen peroxide, stirring and reacting at 50°C for 50 minutes, and then performing solid-liquid separation. The obtained solid was washed with ethanol and then dried to obtain polythiophene-coated nano-cobalt.

[0095] S3: Pre-treat the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine for 4 minutes, then rinse with anhydrous ethanol and blow dry for use; ultrasonically disperse 10 parts of pre-treated graphene and 3 parts of polythiophene-coated nano-cobalt in a reactor filled with 100 parts of ethanol aqueous solution and stir evenly, then add 0.2 parts of sodium sulfite to the reactor, stir and react for 45 minutes under a nitrogen atmosphere, then filter and wash the solid with anhydrous ethanol 3 times and then vacuum dry; obtain a graphene-loaded nano-cobalt conductive agent.

[0096] S4: 38 parts of melamine polyphosphate, 9 parts of resorcinol and 10 parts of conductive agent are ultrasonically dispersed in acetone, uniformly reacted at 60°C for 5 hours, centrifuged for solid-liquid separation, then washed with ethanol and dried to obtain a flame retardant conductive agent.

[0097] The polyether polyol was dehydrated under vacuum at 135° C. until the moisture content was 0.4%, thereby obtaining a treated polyether polyol.

[0098] 2.3 parts of catalyst stannous octoate, 100 parts of polyether polyol, and 2 parts of antioxidant 1010 were added into a reaction kettle, and reacted at 230° C. for 1.5 hours to obtain a reaction material.

[0099] 16 parts of flame retardant conductive agent, 30 parts of isocyanate, 1.5 parts of foaming agent water and 3 parts of foam stabilizer dimethyl silicone oil were added to the reaction material for foaming at a foaming temperature of 83° C. and a reaction time of 25 min to obtain a foamed body.

[0100] The foamed body was aged at 50°C to obtain foam.

[0101] Compared with Example 4, Comparative Example 1 omitted the process of treating the nano-cobalt powder with oleic acid in step S1, and the other process parameters and conditions were the same.

[0102] Comparative Example 2

[0103] S1: Take 3 parts of nano cobalt powder and put them into a reactor, add a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9, and then disperse them by ultrasonic. After reacting for 50 minutes, filter and wash the product with anhydrous ethanol twice and then vacuum dry to obtain oleic acid-nano cobalt; the mass ratio of nano cobalt powder to oleic acid is 18:1.

[0104] S2: Ultrasonic dispersion of 3 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 6 parts of acrylamide and 0.15 parts of hydrogen peroxide, stirring and reacting at 50°C for 50 minutes, and then performing solid-liquid separation. The obtained solid was washed with ethanol and then dried to obtain polyacrylamide-coated nano cobalt.

[0105] S3: Pre-treat the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine for 4 minutes, then rinse with anhydrous ethanol and blow dry for use; ultrasonically disperse 10 parts of pre-treated graphene and 3 parts of polyacrylamide-coated nano-cobalt in a reactor filled with 100 parts of ethanol aqueous solution and stir evenly, then add 0.2 parts of sodium sulfite to the reactor, stir and react for 45 minutes under a nitrogen atmosphere, then filter and wash the solid with anhydrous ethanol three times and then vacuum dry; obtain a graphene-loaded nano-cobalt conductive agent.

[0106] S4: 38 parts of melamine polyphosphate, 9 parts of resorcinol and 10 parts of conductive agent are ultrasonically dispersed in acetone, uniformly reacted at 60°C for 5 hours, centrifuged for solid-liquid separation, then washed with ethanol and dried to obtain a flame retardant conductive agent.

[0107] The polyether polyol was dehydrated under vacuum at 135° C. until the moisture content was 0.4%, thereby obtaining a treated polyether polyol.

[0108] 2.3 parts of catalyst stannous octoate, 100 parts of polyether polyol, and 2 parts of antioxidant 1010 were added into a reaction kettle, and reacted at 230° C. for 1.5 hours to obtain a reaction material.

[0109] 16 parts of flame retardant conductive agent, 30 parts of isocyanate, 1.5 parts of foaming agent water and 3 parts of foam stabilizer dimethyl silicone oil were added to the reaction material for foaming at a foaming temperature of 83° C. and a reaction time of 25 min to obtain a foamed body.

[0110] The foamed body was aged at 50°C to obtain foam.

[0111] Comparative Example 2 Compared with Example 4, acrylamide was used instead of thiophene to coat the nano-cobalt, and the other process parameters and conditions were the same.

[0112] Comparative Example 3

[0113] S1: Take 3 parts of nano cobalt powder and put them into a reactor, add a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9, and then disperse them by ultrasonic. After reacting for 50 minutes, filter and wash the product with anhydrous ethanol twice and then vacuum dry to obtain oleic acid-nano cobalt; the mass ratio of nano cobalt powder to oleic acid is 18:1.

[0114] S2: Ultrasonic dispersion of 3 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 6 parts of thiophene and 0.15 parts of hydrogen peroxide, stirring and reacting at 50°C for 50 minutes, and then performing solid-liquid separation. The obtained solid was washed with ethanol and then dried to obtain polythiophene-coated nano cobalt.

[0115] S3: Pre-treat the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine for 4 minutes, then rinse with anhydrous ethanol and blow dry for use; ultrasonically disperse 10 parts of pre-treated graphene and 3 parts of polythiophene-coated nano-cobalt in a reactor filled with 100 parts of ethanol aqueous solution and stir evenly, then add 0.2 parts of sodium sulfite to the reactor, stir and react for 45 minutes under a nitrogen atmosphere, then filter and wash the solid with anhydrous ethanol 3 times and then vacuum dry; obtain a graphene-loaded nano-cobalt conductive agent.

[0116] The polyether polyol was dehydrated under vacuum at 135° C. until the moisture content was 0.4%, thereby obtaining a treated polyether polyol.

[0117] 2.3 parts of catalyst stannous octoate, 100 parts of polyether polyol, and 2 parts of antioxidant 1010 were added into a reaction kettle, and reacted at 230° C. for 1.5 hours to obtain a reaction material.

[0118] 16 parts of a mixture of melamine polyphosphate and a conductive agent (in a ratio of 38 to 10), 30 parts of isocyanate, 1.5 parts of water as a foaming agent and 3 parts of dimethyl silicone oil as a foam stabilizer were added to the reaction material for foaming at a foaming temperature of 83° C. and a reaction time of 25 min to obtain a foamed body.

[0119] The foamed body was aged at 50°C to obtain foam.

[0120] Compared with Example 4, in Comparative Example 3, the process of cross-linking melamine polyphosphate with the conductive agent in step S4 is omitted, and the other process parameters and conditions are the same.

[0121] The foams in Examples 1-4 and Comparative Examples 1-3 were subjected to performance testing;

[0122] The flame retardant performance test is as follows:

[0123] The limiting oxygen index (LOI) was determined according to GB / T2406-1993; the oxygen index measuring instrument HC-2 was purchased from Nanjing Jiangning District Analytical Instrument Factory.

[0124] The horizontal combustion test of UL94 foam material refers to GB / T8332-2008, and the horizontal combustion tester CZF-3 is purchased from Nanjing Jiangning District Analytical Instrument Factory.

[0125] Conductivity test: The test was carried out using a FT-3120 four-probe measuring instrument purchased from Ningbo Ruikewei Intelligent Technology Co., Ltd.

[0126] Conductivity: Connect the two ends of the test sample to the positive and negative electrodes of the electrochemical workstation with copper wires, call the single potential step chronoamperometry, set the measurement voltage U=10V, the measurement time is 10s, take the average value after the current curve stabilizes, and calculate the conductivity.

[0127] The performance test results are shown in Table 1 below.

[0128]

[0129] As can be seen from Table 1, due to the lack of the step of activating nano-cobalt with oleic acid in Comparative Example 1, the nano-cobalt agglomerates and cannot exert its electrical conductivity and catalytic decomposition of melamine polyphosphate, resulting in poor flame retardancy and electrical conductivity.

[0130] In Comparative Example 2, since the nano-cobalt is wrapped with polyacrylamide, compared with Example 4 which is coated with polythiophene, the polyacrylamide has poor conductivity and cannot exert the conductive properties of the nano-materials, resulting in a decrease in its conductivity. On the other hand, polyacrylamide lacks conjugated π orbitals and has poor compatibility with graphene loading, resulting in a low actual nano-cobalt content in the conductive agent, resulting in insufficient synergistic flame retardancy and a decrease in flame retardancy.

[0131] Comparative Example 3 lacks the step of cross-linking the flame retardant and melamine polyphosphate, resulting in the two components being dispersed in the polyurethane matrix, and the synergistic effect is reduced, thereby reducing its flame retardant properties, but still has good conductive properties.

[0132] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A multifunctional conductive foam, characterized in that: From top to bottom, it includes conductive cloth, foam, adhesive layer and isolation layer. The foam comprises: 100 parts of polyether polyol, 25-35 parts of isocyanate, 10-18 parts of flame retardant conductive agent, 1-2 parts of foaming agent, 2-2.5 parts of catalyst, 1-5 parts of antioxidant and 2-5 parts of foam stabilizer; The preparation method of the flame retardant conductive agent comprises the following steps: S1: 2-4 portions of nano-cobalt powder are put into a reactor, and a mixed solution of oleic acid and anhydrous ethanol is added for ultrasonic dispersion. After the reaction is completed, the product is filtered and washed with anhydrous ethanol, and vacuum dried to obtain oleic acid-nano-cobalt; the mass ratio of the nano-cobalt powder to oleic acid is 12-20:1; S2: ultrasonically dispersing 2-4 parts of oleic acid-nano cobalt in 200 parts of deionized water, then adding 5-8 parts of thiophene and 0.1-0.2 parts of hydrogen peroxide, stirring for reaction, and then performing solid-liquid separation, washing the obtained solid with ethanol and drying it to obtain polythiophene-coated nano cobalt; S3: pre-treating the three-dimensional graphene foam in an air atmosphere in a plasma treatment machine, then rinsing with anhydrous ethanol and drying for standby use; ultrasonically dispersing 10 parts of the pre-treated graphene and 2-4 parts of the polythiophene-coated nano-cobalt in a reactor filled with an ethanol aqueous solution and stirring evenly, then adding 0.1-0.3 parts of sodium sulfite to the reactor, stirring and reacting under a nitrogen atmosphere, then filtering and washing the solid with anhydrous ethanol, and vacuum drying; obtaining a graphene-loaded nano-cobalt conductive agent; S4: ultrasonically dispersing 30-40 parts of melamine polyphosphate, 8-10 parts of resorcinol and 10 parts of the conductive agent in acetone, performing a cross-linking reaction for a period of time, and then centrifuging for solid-liquid separation, washing the solid with ethanol and then drying to obtain the flame retardant conductive agent.

2. The multifunctional conductive foam according to claim 1, characterized in that: The specific process of step S1 is to take 2-4 parts of nano cobalt powder and put it into a reactor, add a mixed solution of oleic acid and anhydrous ethanol in a volume ratio of 1:9, and ultrasonically disperse it, react for 30-60 minutes, filter the product, wash it with anhydrous ethanol 2-3 times, and then vacuum dry it to obtain oleic acid-nano cobalt; the mass ratio of the nano cobalt powder to oleic acid is 12-20:

1.

3. The multifunctional conductive foam according to claim 1, characterized in that: The specific process of step S2 is: ultrasonically disperse 2-4 parts of oleic acid-nano cobalt in 200 parts of deionized water, then add 5-8 parts of thiophene and 0.1-0.2 parts of hydrogen peroxide, stir and react at 40-60° C. for 40-60 minutes, then perform solid-liquid separation, wash the obtained solid with ethanol and then dry to obtain polythiophene-coated nano cobalt.

4. The multifunctional conductive foam according to claim 1, characterized in that: The specific process of step S3 is: pre-treating the three-dimensional graphene foam in an air atmosphere for 2-5 minutes in a plasma treatment machine, then rinsing with anhydrous ethanol and drying for standby use; ultrasonically dispersing 10 parts of the pre-treated graphene and 2-4 parts of the polythiophene-coated nano-cobalt in a reactor containing 100 parts of an ethanol aqueous solution and stirring evenly, then adding 0.1-0.3 parts of sodium sulfite to the reactor, stirring and reacting for 30-60 minutes under a nitrogen atmosphere, then filtering and washing the solid with anhydrous ethanol 2-3 times and then vacuum drying; A graphene-loaded nano-cobalt conductive agent is obtained.

5. The multifunctional conductive foam according to claim 1, characterized in that: The specific process of step S4 is: ultrasonically disperse 30-40 parts of melamine polyphosphate, 8-10 parts of resorcinol and 10 parts of the conductive agent in acetone, uniformly react at 50-70° C. for 3-6 hours, centrifuge for solid-liquid separation, wash the solid with ethanol 2-3 times and then dry to obtain a flame retardant conductive agent.

6. The multifunctional conductive foam according to claim 1, characterized in that: The conductive cloth layer is plain conductive cloth with a thickness of 40 μm-120 μm; the adhesive layer is a pressure-sensitive adhesive or a hot-melt adhesive with a thickness of 10-15 μm; the isolation layer is release paper with a thickness of 20-30 μm.

7. The multifunctional conductive foam according to claim 1, characterized in that: The antioxidant is one of antioxidant 5057, antioxidant 168 and antioxidant 1010.

8. The multifunctional conductive foam according to claim 1, characterized in that: The foam stabilizer is one or more of polyacrylamide and dimethyl silicone oil.

9. The multifunctional conductive foam according to claim 1, characterized in that: The catalyst is one or more of stannous octoate, stannous isooctanoate and dibutyltin dilaurate; The blowing agent is water or a mixture of water and 1,1-dichloro-1-fluoroethane.

Citation Information

Patent Citations

  • Inert foamed cotton with high damping property and preparation method of inert foamed cotton

    CN104725594A

  • Graphene-conductive polymer composite and preparation method thereof

    CN107641824A